Empathy in health professionals and students: factorial analysis of the Brazilian version of Interpersonal Reactivity Index (Research, Society and Development, 2022)
This study aims to evaluate the empathy of health undergraduated students and professionals in Curitiba and to verify the factorial structure of the Brazilian version of Interpersonal Reactivity Index in this population. The participants were 886 individuals, female (64.2%) and male, aged 18 to 65 years (mean = 25.2 years; standard deviation = 7.8), being 672 health undergraduated students and 214 health professionals. The instrument used was the Multidimensional Scale of Interpersonal Reactivity. Students have higher levels of global empathy, personal distress and fantasy than professionals. The results related to the differences between the female and male do not match what is presented in the national and international scientific literature, which can be attributed to the higher age observed in the women. Anyway, the scale has adequate internal consistency and acceptable psychometric indicators to be used in this population.